# Rearranging Formula, making x the subject

### Rearranging Formula, making x the subject

Hi, we were rearranging formula to make $x$ the subject and for one equation our answer was different to our lecturers, but they failed to explain why they were right and we were wrong- if someone could that would be great.
When making $x$ the subject we're told to "do the opposite" to achieve this.

The equation with our working:

$y=5(x+3)$

$\frac{y}{5}=x+3$

$\frac{y}{5}-3=x$

Replacing $x$ with 2 as an example to test our result:

$y=5(2+3)$ (or) $y=5$x$5$ (or) $y=25$

$\frac{25}{5}=5$, $-3=2$, $x=2$
Guest

### Re: Rearranging Formula, making x the subject

You are right!
Here is the explanation:

1. You divide the both sides by 5
and since the both sides are equal the result is equal too.
$\frac{y}{5} = \frac{5(x + 3)}{5}$

$\frac{y}{5} = (x + 3)$
2. You subtract the both sides by -3

$\frac{y}{5} - 3 = x + 3 - 3$

$\frac{y}{5} - 3 = x$
Guest

### Re: Rearranging Formula, making x the subject

Note: I wanted to write
2. You subtract the both sides by 3 (not by -3)
Guest

### Re: Rearranging Formula, making x the subject

(OT) Thanks for confirming!
Guest